The spherical α-Fe2O3 nanomaterials prepared by hydrolysis route and hydrothermal route for lithium-ion batteries. (2nd January 2016) - Hu, Chuanyue; Guo, Jun; Zhong, Hongbin; Chen, Zhanjun; Wen, Jin
Abstract : The spherical α-Fe2 O3 nanoparticles with the average particle size of 50 nm were successfully prepared by the forced hydrolysis route and hydrothermal route. Firstly, a crystallised FeOOH precursor was prepared through a forced hydrolytic route. Then, hydrothermal method was carried out with the FeOOH precursor to produce spherical iron oxide in the mixture of water and ethanol. The structure and electrochemical performance of spherical α-Fe2 O3 materials were characterised by X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM) and galvanostatic cell cycling methods. The prepared α-Fe2 O3 material exhibited a excellent electrochemical performance. The reversible capacity was 1421.3 mAh g −1 at 0.1 C ratio in the first cycle and 632.1 mAh g −1 after 50 cycles at 0.1, 0.2, 0.5, 1.0 and 2.0 C ratio (1 C ratio is defined as 6 Li + per hour; 1005 mAh g −1 ).